Karakteristik Pasien Limfoma Maligna di Rumah Sakit Umum Daerah Prof.Dr.Margono Soekarjo Purwokerto Jawa Tengah Tahun 2024 - Setyowati, Hapsari Galih (Green Publisher Indonesia, 2025)
Malignant lymphoma is a hematological malignancy that requires local epidemiological characterization for optimization of diagnostic and therapeutic strategies. Comprehensive data on characteristics of malignant lymphoma patients in Indonesia remains limited, particularly in Central Java region. This study aims to identify and describe demographic and clinical characteristics of malignant lymphoma patients diagnosed at Prof. Dr. Margono Soekarjo Regional General Hospital. This study employed a descriptive cross-sectional design with retrospective approach. Secondary data were collected from medical records and anatomical pathology examination results of all malignant lymphoma patients during January-December 2024 period. Univariate analysis was performed using SPSS with frequency distribution and percentage presentation for age, gender, histopathological type, and tumor location variables. Among 176 malignant lymphoma patients, the 51-60 years age group was the most prevalent (35%), with balanced gender distribution between males and females (50% each). Non-Hodgkin Lymphoma (NHL) dominated with 148 cases (79.1%), where B-cell Non-Hodgkin Lymphoma was the most common subtype (63.1%). Most cases were classified as high grade (79%) and extranodal locations were more frequently found (54%) with GIT and liver as the most common sites (20.5%). Characteristics of malignant lymphoma at Prof. Dr. Margono Soekarjo Regional General Hospital demonstrate dominance of B-cell type NHL in middle-aged adults with balanced gender distribution and extranodal location predominance, providing important local epidemiological insights for clinical management strategies.